Penggunaan Fuzzy Logic & Metode Mamdani untuk Menghitung Pembelian, Penjualan dan Persediaan - Maria Yus Trinity Irsan; Matius Irsan Kasau; Ika Pratiwi Simbolon (President University Press, 2019)
Fuzzy Logic is a development of Binary Logic that can be used to analyze data in research in both the exact and social fields. In this study, fuzzy logic is used to analyze data in a